2009
DOI: 10.1186/1756-0500-2-191
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime intimate partner violence exposure, attitudes and comfort among Canadian health professions students

Abstract: BackgroundIntimate partner violence (IPV) is a widespread public health problem and training of health professions students has become common. Understanding students' prior knowledge, attitudes and personal exposure to IPV will aid educators in designing more effective curriculum. As interprofessional educational efforts proliferate, understanding differences across disciplines will be critical.FindingsStudents in the schools of Medicine, Nursing and Rehabilitation at a university in Ontario attend an annual d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
1
6
0
4
Order By: Relevance
“…Nursing students experienced lack of the confidence in recognizing and responding to abuse, and felt in insufficiently prepared to deal with DV (15). Apart from these studies, Gerber and Tan (28) determined that nursing students have very positive attitudes towards domestic violence and abused women. As a result of these studies, it can be said that the knowledge and attitudes of the health science students are negative in general.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing students experienced lack of the confidence in recognizing and responding to abuse, and felt in insufficiently prepared to deal with DV (15). Apart from these studies, Gerber and Tan (28) determined that nursing students have very positive attitudes towards domestic violence and abused women. As a result of these studies, it can be said that the knowledge and attitudes of the health science students are negative in general.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that the majority of students believed it was their role to address DV in practice, but lacked knowledge related to the impact on the victim: 12% of nurses and 20% of the rehabilitation students could not understand why victims stayed in abusive relationships. It was also reported that personal experience of DV did not affect the level of comfort in addressing the issue (Gerber & Tan ). Another Canadian study with over 200 medical and surgical students who completed an online survey found many misconceptions about DV, including myths about traits of victims (Sprague et al .…”
Section: Introductionmentioning
confidence: 99%
“…Y por último, un tratante no entrenado en violencia, que aun frente a la evidencia, busca retornar a su equilibrio "no registrando" o "minimizando" lo que observa y asumiendo que la víctima posee más poder del que en realidad tiene (Barudy, 1998;Ravazzola, 1997 A nivel nacional no existe información sistematizada en relación a cuánta formación reciben los médicos en su pre y postgrado en relación a VIF-AS. Hay acuerdo en la literatura internacional, sin embargo, en que esta formación es escasa, con falta de contenidos en los currículos, y con un abordaje aislado y más bien teórico (Gerber et al, 2009;Hill, 2005;Jamner et al, 2000;Miranda et al 2009;Narayan et al, 2006;Reece et al, 2005).…”
Section: Resultsunclassified
“…-Asumir la responsabilidad de autoformación en VIF-AS según las exigencias de su cargo. (Brandt, 1997;Gerber et al, 2009;Hill, 2005;Jamner et al, 2000;Miranda et al 2009;Reece et al, 2005).…”
Section: Actitudinalunclassified